1998
DOI: 10.1111/j.1151-2916.1998.tb02375.x
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of Grain‐Boundary Bonding in Rare‐Earth‐Doped β‐Si3N4

Abstract: First‐principles molecular orbital calculations are performed by the discrete variational Xalpha method using model clusters of rare‐earth‐doped β‐Si3N4 and the interface between prismatic planes of β‐Si3N4 and intergranular glassy films. On the basis of the total overlap population of each cluster, the rare‐earth ions are implied to be stable in the grain‐boundary model, while they are not stable in the bulk model. These results are consistent with experimental observations showing significant segregation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 12 publications
3
10
0
Order By: Relevance
“…In contrast, the rest of the elements showed the atomic bonding of atoms along the prismatic plane of Si 3 N 4 that is periodic and occurred at two very specific atomic sites, A and B. Sm atoms bond in single‐atom configuration to both positions, whereas Er, Yb, and Lu atoms bond in pairs at A site and singly at B site. Thus, it could be concluded that the segregation tendency of RE ions at the interface increases with increasing atomic number (decreasing ionic radius), which agrees well with the prediction made from the first principle molecular orbital calculations performed by the discrete variation (DV) Xα method: the total chemical bonding strength evaluated by the total overlap population increased by the presence of any RE 3+ at the interface, and it strengthened with increasing atomic number of RE (decreasing ionic radius) 8 …”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…In contrast, the rest of the elements showed the atomic bonding of atoms along the prismatic plane of Si 3 N 4 that is periodic and occurred at two very specific atomic sites, A and B. Sm atoms bond in single‐atom configuration to both positions, whereas Er, Yb, and Lu atoms bond in pairs at A site and singly at B site. Thus, it could be concluded that the segregation tendency of RE ions at the interface increases with increasing atomic number (decreasing ionic radius), which agrees well with the prediction made from the first principle molecular orbital calculations performed by the discrete variation (DV) Xα method: the total chemical bonding strength evaluated by the total overlap population increased by the presence of any RE 3+ at the interface, and it strengthened with increasing atomic number of RE (decreasing ionic radius) 8 …”
Section: Introductionsupporting
confidence: 86%
“…Thus, it could be concluded that the segregation tendency of RE ions at the interface increases with increasing atomic number (decreasing ionic radius), which agrees well with the prediction made from the first principle molecular orbital calculations performed by the discrete variation (DV) Xa method: the total chemical bonding strength evaluated by the total overlap population increased by the presence of any RE 31 at the interface, and it strengthened with increasing atomic number of RE (decreasing ionic radius). 8 The next fundamental question is what the ''catalytic effect'' is. Segregation/adsorption occurs as a result of decreasing the free energy of the total system.…”
Section: Introductionmentioning
confidence: 99%
“…The results of Nakayasu et al 10 demonstrate how Ln 3ϩ ions are more stable at the interfaces and less stable in the Si 3 N 4 matrix. Benco 9 states that oxygen present along grain boundaries in Si 3 N 4 has a destabilizing effect on the bonding characteristics if associated antibonding interactions are not prevented.…”
Section: Introductionmentioning
confidence: 96%
“…8 -14 Using a Hartree-Fock periodic approach with extended Hückel tight-binding approximation 8,9 and molecular dynamic calculations with a pair-potential set approach, 10 atomic positions and grain-boundary bonding characteristics have been determined for a variety of interface-atom coordinations. 8 -14 Using a Hartree-Fock periodic approach with extended Hückel tight-binding approximation 8,9 and molecular dynamic calculations with a pair-potential set approach, 10 atomic positions and grain-boundary bonding characteristics have been determined for a variety of interface-atom coordinations.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, this new information about the atomic structure and bonding characteristics will help verify and refine atomic-structure calculations performed in the past [16][17][18][19][20][21]. A double peak (102eV and 103.5eV) appears in the spectrum taken from atom position A.…”
Section: Resultsmentioning
confidence: 69%